Pengaruh Self-Esteem dan Optimisme Masa Depan Siswa Menengah Kejuruan (SMK) Berbasis Pesantren - Fia Zahrotun Ni'mah; M Arif Khoiruddin (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2021)
Pesantren-based Vocational Schools are educational institutions with advantages expected to have intellectual, skilful graduates ready to work and uphold morality. This study aims to determine how self-esteem affects the future optimism of Pesantren-based vocational high school students. The study used quantitative methods with a sample of 50 students of SMK Al-Mahrusiyah Pondok Pesantren Lirboyo. Random sampling technique with simple regression analysis. The results showed an influence between self-esteem and optimism of 12.2% with a significance of 0.013, meaning that there was a significant contribution of self-esteem and optimism for the future of SMK Al-Mahrusiyah students. The self-esteem level of SMK Al Mahrusiyah students, the majority of students are at a moderate level of self-esteem of 64%, some others have high self-esteem of 20%, and a smaller portion has a low level of self-esteem of 16%.